## Simplify this equation p+p+3 = 13* O 2+p+ 2 = 13 O 2p+ 3 = 13 O 2p = 10

Question

Simplify this equation p+p+3 = 13*
O 2+p+ 2 = 13
O 2p+ 3 = 13
O
2p = 10

in progress 0
6 days 2021-11-25T20:27:53+00:00 1 Answer 0 views 0

P=3 hope this helps! Sorry if I get it wrong. Hope I get brainliest! 😀

Step-by-step explanation:

Simplifying

3p + -1 = 5(p + -1) + -2(7 + -2p)

-1 + 3p = 5(p + -1) + -2(7 + -2p)

-1 + 3p = 5(-1 + p) + -2(7 + -2p)

-1 + 3p = (-1 * 5 + p * 5) + -2(7 + -2p)

-1 + 3p = (-5 + 5p) + -2(7 + -2p)

-1 + 3p = -5 + 5p + (7 * -2 + -2p * -2)

-1 + 3p = -5 + 5p + (-14 + 4p)

-1 + 3p = -5 + -14 + 5p + 4p

-5 + -14 = -19

-1 + 3p = -19 + 5p + 4p-1 + 3p = -19 + 9p

Solving

-1 + 3p = -19 + 9p

Solving for variable ‘p’.

Move all terms containing p to the left, all other terms to the right.

Add ‘-9p’ to each side of the equation.

-1 + 3p + -9p = -19 + 9p + -9p

Combine like terms: 3p + -9p = -6p

-1 + -6p = -19 + 9p + -9p

Combine like terms: 9p + -9p = 0

-1 + -6p = -19 + 0

-1 + -6p = -19

Add ‘1’ to each side of the equation.

-1 + 1 + -6p = -19 + 1

Combine like terms: -1 + 1 = 0

0 + -6p = -19 + 1

-6p = -19 + 1

Combine like terms: -19 + 1 = -18

-6p = -18

Divide each side by ‘-6’.

p = 3

Simplifying

p = 3